2013
DOI: 10.1016/j.neubiorev.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding smell—The olfactory stimulus problem

Abstract: Please cite this article as: Auffarth, B., Understanding smell -the olfactory stimulus problem, Neuroscience and Biobehavioral Reviews (2013), http://dx.doi.org/10.1016/j.neubiorev.2013.06.009. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 244 publications
(221 reference statements)
0
41
0
Order By: Relevance
“…The bias for vision comes primarily from the fact that this modality is the predominant human sense [53]. Because olfaction is often a largely unconscious process in humans [54], perceptual dimensions of odours are not well understood and olfaction lacks an intrinsic spatial topology in comparison to other modalities [55]. This has resulted in the importance of olfaction being ignored in many systems.…”
Section: Discussionmentioning
confidence: 99%
“…The bias for vision comes primarily from the fact that this modality is the predominant human sense [53]. Because olfaction is often a largely unconscious process in humans [54], perceptual dimensions of odours are not well understood and olfaction lacks an intrinsic spatial topology in comparison to other modalities [55]. This has resulted in the importance of olfaction being ignored in many systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although humans have an outstanding sense of smell (Sela and Sobel 2010), we often find it difficult to understand and investigate olfaction due to the difficulties in communicating about our olfactory experiences by means of language (Auffarth 2013;Kaeppler and Mueller 2013; though see Koulakov et al 2011;Majid and Burenhult 2014). In fact, it has been suggested that olfactory experience (odour identification, discrimination or even just the perception of an odour's intensity and pleasantness) may benefit substantially from the availability of visual cues, specifically colour cues, thus suggesting the importance of the crossmodal effects that may take place between these two sensory modalities (see Spence 2011; Zellner 2013 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…These matrices here will be represented as perceptual matrix (P), where rows represent molecules (m) and columns percepts (p). Further, in the databases were combined into a common representation of matrix of 3001 molecules and 520 perceptual descriptors.. Olfaction has been a very subjective and contentious of our senses owing to large variations in its reporting which is partly due to the fact that people experience it very differently [9,10,11]. The only non-invasive method of its reporting in humans is via language.…”
Section: Database Descriptionmentioning
confidence: 99%
“…Olfaction has been a very subjective and contentious of our senses owing to large variations in its reporting which is partly due to the fact that people experience it very differently [9,10,11]. The only non-invasive method of its reporting in humans is via language.…”
Section: Introductionmentioning
confidence: 99%